Bridged emulsion gels from polymer–nanoparticle enabling large-amount biomedical encapsulation and functionalization - Chuchu Wan; Si He; Quanyong Cheng; Kehan Du; Yuhang Song; Xiang Yu; Hao Jiang; Caili Huang; Jiangping Xu; Cong Ma; Jintao Zhu (Nature Communications)
Abstract Large-amount encapsulation and subsequent expressing are common characteristics for many biomedical applications, such as cosmetic creams and medical ointments. Emulsion gels can accomplish that, but often undergo exclusive, complex, multiple synthesis steps, showing extremely laborious and non-universal. The method here is simple via precisely interfacial engineering in homogenizing a nanoparticle aqueous dispersion and a polymer oil solution, gaining interfacial 45° three-phase-contact-angle for the nanoparticle that can bridge across oil emulsions’ interfaces and ultimately form interconnected macroscopic networks. Their bridged skeletons and rheology are tunable over a vast range and deterministic on the basis of components’ inputs. Furthermore, emulsion gels with high encapsulation and storage ability encapsulating active sunscreen ingredients, as a proof-of-concept, outperform commercial products. The ease (only seconds by strongly mixing two solutions) and the versatile chemical selection of our synthetic emulsion gels suggest an exciting general, scalable strategy for the next-generation cosmetic, ointment or otherwise food gel systems.